Bentuk Komunikasi Organisasi Melalui Kegiatan Tanggungjawab Sosial Perusahaan Untuk Pemberdayaan Masyarakat (Studi PT PERTAMINA REFINERY Unit VI BALONGAN) - I Situmeang; D.P. Lubis; A. Saleh (Jurnal Komunikasi Pembangunan, 2012)
Abstrak Corporate social responsibility is one of organizational communication form. Through this organizational communication form corporate hopes can build a good relationship with community. The main problem from this research was: what Form/Type of organizational communication performed by PT Pertamina Refinery Balongan to empowering community? The objective of this research was: to analyze form/type of organizational communication conducted by PT Pertamina Refinery Balongan to empowering community. This research was designed aa description research. Primary data was obtained through interview, observation and documentasi. Secondary data obtained from Pertamina company profile, CSR profile and literature study. The resulted output from this research was: in order to build a good relationship between corporate and community PT Pertamina Refinery Balongan conducted organizational communication by using PENCILS mix Principle (publication, event, news, community involvement, inform or image, lobbying and negotiation, social responsibility). Corporate Social Responsibility conducted by PT Pertamina Refinery Balongan covered economic sector, social sector, and environmental sector. The main goal from this corporate social responsibility is to empower the people of Balongan. Key Words: Organizational Communication, Corporate Social Responsibility, Community Participation